2008
DOI: 10.1007/s00264-008-0607-y
|View full text |Cite
|
Sign up to set email alerts
|

Ten different hip resurfacing systems: biomechanical analysis of design and material properties

Abstract: This study gives an overview of the main macroand microstructural differences of ten commercially available total hip resurfacing implants. The heads and cups of resurfacing hip implants from ten different manufacturers were analysed. The components were measured in a coordinate measuring machine. The microstructure of the heads and cups was inspected by scanning electron microscopy. The mean radial clearance was 84.86 μm (range: 49.47-120.93 μm). The implants were classified into three groups (low, medium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…The head and cup are not perfectly spherical and smooth; these irregularities are defined as deviation of roundness and surface roughness and range from 1-5 mm and 0.01-0.03 mm, respectively. 9 Carbon content and manufacturing method (wrought or cast) influence the metallic microstructure and mechanical properties. With increasing carbon content, the carbides (very hard metal-carbon compounds) increase in amount and size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The head and cup are not perfectly spherical and smooth; these irregularities are defined as deviation of roundness and surface roughness and range from 1-5 mm and 0.01-0.03 mm, respectively. 9 Carbon content and manufacturing method (wrought or cast) influence the metallic microstructure and mechanical properties. With increasing carbon content, the carbides (very hard metal-carbon compounds) increase in amount and size.…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations were reported using hip simulators. 9,38 Two other simulator studies reported less wear for cast compared to wrought implants. 20,33 Dowson et al 11 did not observe a difference between as-cast and wrought implants in a hip simulator.…”
Section: Meta-analysis Of Design and Manufacturing-related Paramentermentioning
confidence: 99%
“…It is hoped that, as these modern techniques evolve and become more user-friendly, reduced surgeon error in implant positioning should decrease the incidence of wear-related failures. The many nuances [32] of implant design and materials constitute the third risk factor for resurfacing failures. Our past experience [19] has shown that changes to materials processing can be detrimental to implant survivorship.…”
Section: Discussionmentioning
confidence: 99%
“…According to standards, the roughness (Ra) and roughness must lie within 0.02-0.036 μm and-and 0.9-7.3μm respectively to keep wear within acceptable limits. This is a critical factor in the material, construction, technology development and optimization of the acetabular shell [10,11]. Investigation on Co-Cr-Mo showed various factors such as clearance, head size, carbon content, and manufacturing method had an influence on metal-on-metal wear behaviour.…”
Section: Introductionmentioning
confidence: 99%